2021
DOI: 10.1021/acs.iecr.1c01734
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Superhydrophobic Composite Coatings with Remarkable Passive Heat Dissipation and Anticorrosion Properties

Abstract: Effective surface passive heat dissipation and durable superhydrophobicity are highly desired for promoting more flexible applications of power-intensive energy systems of aluminum and aluminum-based composites. Herein, we developed a simple and universal approach to fabricate durable superhydrophobic composite coatings composed of hexamethyldisilazane-modified silicon carbide nanowires (HMDS-SiCNWs) and fluorosilicone (FSi) resin. The as-prepared superhydrophobic coating on aluminum substrates exhibited excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In nature, there are many examples of superhydrophobic surfaces possessing this special self-cleaning property such as butterfly wings, shark skin, and lotus leaves. It is revealed that this property of the lotus leaf or the “Lotus effect” results from the rough morphology and the hydrophobic epicuticular wax covering the entire surface leaf. Inspired by this discovery, many researchers have mimicked the “Lotus effect” by designing and fabricating artificial superhydrophobic surfaces using the combination of micro/nano or hierarchical morphologies and low surface energy materials. However, besides the elemental factors constituting the superhydrophobicity of a surface-like surface roughness and hydrophobic material coating, the superhydrophobic surface has to be transparent for applications requiring high optical transmittance like solar cell panel protection . Therefore, several strategies for fabricating flexible transparent superhydrophobic structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, there are many examples of superhydrophobic surfaces possessing this special self-cleaning property such as butterfly wings, shark skin, and lotus leaves. It is revealed that this property of the lotus leaf or the “Lotus effect” results from the rough morphology and the hydrophobic epicuticular wax covering the entire surface leaf. Inspired by this discovery, many researchers have mimicked the “Lotus effect” by designing and fabricating artificial superhydrophobic surfaces using the combination of micro/nano or hierarchical morphologies and low surface energy materials. However, besides the elemental factors constituting the superhydrophobicity of a surface-like surface roughness and hydrophobic material coating, the superhydrophobic surface has to be transparent for applications requiring high optical transmittance like solar cell panel protection . Therefore, several strategies for fabricating flexible transparent superhydrophobic structures have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the lotus leaf effect [17], superhydrophobic materials with high water repellency abilities can achieve self-cleaning [18], anti-corrosion [19], anti-biofouling [20], anti-fogging [21] and oil-water separation [22], and so on. Preparation of superhydrophobic materials with oil-water separation ability have become a research topic.…”
Section: Introductionmentioning
confidence: 99%
“…In these above obtained properties, people can pay more attention to protect the matrix from the impurity. Numerous studies have shown that the common preparation methods for superhydrophobic coatings includes etching‐modified, sol‐gel, electrical desposition, laser process and hydrothermal in‐situ growth [19,20] . For example, Tang et al [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the common preparation methods for superhydrophobic coatings includes etchingmodified, sol-gel, electrical desposition, laser process and hydrothermal in-situ growth. [19,20] For example, Tang et al [21] used a laser chemical method to ablate and assist in the decomposition of stearic acid on 316 L stainless steel to obtain superhydrophobic micropatterns, with an optimal sample contact angle of 153.9°. The obtained superhydrophobic surface can capture air and form cavitation in the multi-layer structure, so as to prevent the infiltration of external substances and improve the corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%